Development of self-report assessment tool for anxiety among adolescents: Indonesian version of the Zung self-rating anxiety scale - Anggi Setyowati; Min-Huey Chung; Ah. Yusuf (AOSIS, 2019)
Anxiety is common among adolescents. Self-report anxiety scales are needed to screen and prevent adolescents sinking into worse mental health. The purpose of this study was to assess the psychometric properties of Indonesia Zung Self-rating Anxiety Scale (SAS), including translation, validity, reliability and receiver operating characteristics (ROC). We used cross-sectional study and correlational design in this study. Total sample was 1,000 adolescents in junior and senior high school. The SAS was translated into Bahasa Indonesia based on World Health Organization guidelines. SAS and the Indonesia version of Beck Depression Inventori-(BDI) II questionnaires were used to develop construct validity. Correlation between item score and total score was used to establish convergent validity. Cronbach's alpha was used to calculate reliability and ROC curves were used to examine cut-off point of SAS. Construct validity showed positive correlation between the SAS and Indonesia version of BDI II scores. Convergent validity showed positive correlation between each item and total score. Cronbach's alpha 0.691 and the ROC 36.5. Thus, the Indonesia version of SAS provides a reliable and valid tool to screen anxiety among adolescents.